A right triangle with legs measuring 3 units and 4 units has a hypotenuse measuring 5 units.
You need to find a point which has a difference in x and y of 3 and 4 or 4 and 3 from the point A(2, 6).
Look at (5, 2) and compare with A(2, 6).
Difference in x: 5 - 2 = 3
Difference in y: 6 - 2 = 4
Since the differences in x and y are 3 and 4, the hypotenuse will measure 5.
Answer: (5, 2)
Answer:
Step-by-step explanation:
Given
Equation to reflect the sum:
The answer is 25 male participants
A. -10
B. 10
C. 2
O D. -2
Answer:
B because when you compare y= mx+ c where M is the slope or gradient
A.
12x – 29
B.
12 + 12 • 17
C.
12x – 12 • 17
D.
12x – 17
Answer:
18-5i
Step-by-step explanation:
Answer: 12-i
12-(√-1)
Step-by-step explanation:
Original Question
Split
Solve for square root
Subtract
You can substitute for i
Substitute
2. Find the value of n
Answer:
For 1: The first term is 10 and the common difference is
For 2: The value of n is 27
Step-by-step explanation:
The n-th term of the progression is given as:
where,
is the first term, n is the number of terms and d is the common difference
The sum of n-th terms of the progression is given as:
where,
is the sum of nth terms
The 11th term of the progression:
.......(1)
Sum of first 4 numbers:
......(2)
Forming equations:
( × 8)
The equations become:
Solving above equations, we get:
Putting value in equation (1):
Hence, the first term is 10 and the common difference is
The nth term is given as:
Solving the above equation:
Hence, the value of n is 27
The value of n when the nth term of the progression is 49 is 22.
The 11th term of the progression (a11) is 25.
The sum of the first 4 terms (S4) is 49.
The nth term (an) is 49.
Let's find the answers to your questions:
Find the first term of the progression (a1) and the common difference (d):
We know that the nth term of an AP can be expressed as:
an = a1 + (n - 1)d
Substituting the values:
a11 = a1 + (11 - 1)d
25 = a1 + 10d
Now, we need to find a1 and d. We'll also use the information that the sum of the first 4 terms (S4) is 49. In an AP, the sum of the first n terms (Sn) can be expressed as:
Sn = (n/2)[2a1 + (n - 1)d]
For S4:
49 = (4/2)[2a1 + (4 - 1)d]
49 = 2[2a1 + 3d]
Now, we have two equations:
25 = a1 + 10d
49 = 2[2a1 + 3d]
Let's solve this system of equations to find a1 and d.
1. First, rearrange the first equation to isolate a1:
a1 = 25 - 10d
Now, substitute this expression for a1 into the second equation:
49 = 2[2(25 - 10d) + 3d]
Simplify and solve for d:
49 = 2[50 - 20d + 3d]
49 = 2[50 - 17d]
49 = 100 - 34d
34d = 100 - 49
34d = 51
d = 51/34
d = 3/2
2. Now that we have the common difference (d), we can find a1 using the first equation:
a1 = 25 - 10d
a1 = 25 - 10(3/2)
a1 = 25 - 15/2
a1 = (50 - 15)/2
a1 = 35/2
a1 = 17.5
So, the first term of the progression (a1) is 17.5, and the common difference (d) is 3/2.
Find the value of n when the nth term of the progression is 49:
We know that an = 49, and we can use the formula for an in an AP:
an = a1 + (n - 1)d
Substitute the values:
49 = 17.5 + (n - 1)(3/2)
49 - 17.5 = (n - 1)(3/2)
31.5 = (n - 1)(3/2)
To isolate n, multiply both sides by (2/3):
(n - 1)(3/2) = 31.5 * (2/3)
(n - 1) = 21
Now, add 1 to both sides to find n:
n = 21 + 1
n = 22
So, the value of n when the nth term of the progression is 49 is 22.
#SPJ3
Answer:
300
Step-by-step explanation:
= 3(6/2)*10^(-6-(-8)=2) = 300